CONDITION AND CORRECTION OF DENTAL STATUS IN ELITE ATHLETES - Safaraliev, R.F.; Mamedov, F.Yu. (World of Medicine and Biology, 2016)
Goal. To study the effect of biologically active macro - and microelements preparations based on propolis to increase the level of specialized dental care for professional athletes, improve athletic performance and improve their quality of life. Methods. The study involved 122 professional sportsmen at the age from 17 to 34 years. Study of the functional state of the salivary glands was carried out before the start of training, hygienic care of oral hygiene and the use of new drugs, as well as immediately after them. To stimulate salivation and improve the hygienic state of the oral cavity in the examined athletes was evaluated the efficacy of the medicinal product based on propolis - "Balm pomegranate" (composition: propolis, extracts maral root, Golden root, aralia, fir needles). Results. The speed of salivation in almost all the surveyed professional athletes on the background of maximum physical exertion and stress disorders characteristic of precompetitive and competitive periods were low and indicative of severe hyposalivation. In the presence of certain diseases of the gastrointestinal tract in the individual cases revealed athletes with a pronounced and very low level of secretion of salivary glands and salivation – dry mouth. Identified in almost all the surveyed athletes mean rate of salivation in all groups showed hyposalivation in the mouth. The main difference of professional athletes that are already disturbed emotional state in the period of intensive training on the background of chronic stress and sometimes even depression was the fact that they have in contrast to individuals not involved in sports professionally, while promoting the salivation amount of allocated saliva, although increased, but only slightly. Was diagnosed fact reduce adverse background unstimulated secretion of saliva in the examined sportsmen in the studied period of stay in a long intense emotional and physical state (2,14±0,020 ml/min in athletes with healthy periodontium without stimulation and before the training and 1.74±0,016 ml/min after, respectively, p
Keywords: periodontium; saliva; hygiene; physical activity; prevention